Relations Between Parenting Styles and Learning Motivation with Social Science Learning Outcomes - Widoresmi, Dinari; Abidin, Zaenal (Elementary School Teacher, 2019)
This research was backgrounded by preliminary research data. It was found that parents were busy working, students were not enthusiastic in learning process, and social science learning outcomes was not optimal. This aim of researchis toreveal the correlation of parenting patterns and learning motivation with Social Science learning outcomes. This type of research is a correlational quantitative research with sample amount of 136 students taken using the quota sampling. Data collection techniques used interview, questionnaires, and documentation. In addition, data analyses used descriptive statistical analysis, product moment correlation, multiple correlation, simple and mutiple regression. The results showed that there were positive and significant correlation between parenting patterns and social science learning outcomes amount of 0.736, learning motivation and social science learning outcomes amount of 0.725, parenting patterns and learning motivation simultaneously with social science learning outcomes amount of 0.805, contribution of parenting patterns with social science learning outcomes amount of 54.2%, contribution of learning motivation with social science learning outcomes amount of 52.5%, contribution of parenting patterns and learning motivation with social science learning outcomes amountof 64.9%. Those can be concluded that there are positive and significant correlation between parenting patterns and learning motivation with Social Science learning outcomes of fourth-grade students in Primary School, Group of Ki Hajar Dewantara, South Kaliwungu Subdistrict, Kendal Regency.